Eksistensi dan Peranan Jaksa Agung Muda Bidang Pidana Militer Pengadilan Koneksitas - Muhammad Rafli; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The existence and role of the Deputy Attorney General for Military Criminal (JAMPIDMIL) Affairs in his duties and functions in the Military Tribunal, as well as explaining the existence and shift in the authority to adjudicate in the koneksitas Court. This research is a normative juridical research, namely legal research conducted by examining library materials or secondary data only. The approach used in this research is a regulatory approach, namely an approach that is carried out by examining all laws and regulations related to the legal issues being discussed (studied) and a case approach. The establishment of JAMPIDMIL itself is expected to create a functional relationship between the Prosecutor and the Oditur as the Public Prosecutor in military cases where later the Attorney General will have the duty to assist in military criminal cases. JAMPIDMIL has the authority to litigate in general courts related to military members who are suspected of committing general criminal offences.Â The Attorney General will have the duty to assist in military offences. This arrangement is an implementation of the principle of a single prosecution system, which means that no other institution has the right to make summons except under the control of the Attorney General as the highest public summoner of the state.